Case Report: Upper limb dysfunction may be caused by chest wall mass excision: An enlightenment from a special case - Wu, Ping-Shang; Yuan, Ling; Xiong, Dan; Gao, Yan-Hong; Xiang, Luan (Frontiers in Oncology, 2022)
Of all the thoracic surgical procedures, chest wall surgery is probably the lowest-risk type. In fact, it is not so. Clinical work also often has the trap of chest wall surgery. An operation to remove a mass in the axilla may result in upper limb disability on the affected side. Here, we report the case of a 47-year-old female patient with a left chest wall adjacent axillary mass, which was considered an abnormal structural lymph node on color ultrasound examination and chest CT. Otherwise, she felt no discomfort. The left upper limb moved freely without being affected by the mass. A routine resection of the tumor was performed after the preoperative examination was completed. After the operation, the incision recovered well. However, the day after the surgery, she developed numbness and pain in her left little finger and ring finger, pain that often kept her from sleeping. The mass was confirmed to be a schwannoma with cystic degeneration by pathology slicing after the operation. By this time, doctors were alerted to the fact that the removal of the chest wall mass had nearly disabled the left upper limb of the patient, which was a great warning to the thoracic surgeon. In this case report, we hope that all surgeons will be cautious and careful and will not trust the imaging diagnosis too much. It is also hoped that the patient understands that some procedures may lead to unexpected complications.